Ultrasonic inspection for ice accretion assessment: effects on direct wave propagation in composite media. (1st July 2022) - Maio, Leandro; Moll, Jochen; Memmolo, Vittorio; Simon, Jonas
Abstract: From aeroplane wings to overhead power lines, through giant blades of wind turbines, a build up of ice can cause problems ranging from impaired performance all the way to catastrophic failure. Therefore, it is of the utmost importance to control or prevent ice formation, especially on the critical areas of a structure. However, de-icing and anti-icing countermeasures can result energetically expensive and hazardous to the environment. In addition, excessive use of such of them will reduce the life of the ice protection system and introduce fatigue to the controlled structures. Thus, in order to manage properly the available resources, it is desirable to have an ice detection system that can both detect ice formation and monitor the thickness of ice on critical surfaces. This would allow acting when it is necessary. Ultrasonic guided-wave-based technique has been proved reliable for ice detection, but approaches to establish ice accretion over time have not been provided yet. The paper investigates the interaction of ultrasonic direct waves in composite plate with ice layers and the effects of ice thickening on the ultrasound propagation. Moreover, the use of metrics is discussed as indicators of ice growth. Highlights: Ultrasound-ice interaction analysis to pave the way towards autonomous detection. Advanced signal processing to gather information about ice effects on Lamb waves. Detection indicators to monitor ice build-up phenomenon and achieve early detection.